Digital-Based Green Accounting and Its Impact on Financial Performance - Lilis Saidah Napisah; Budi Harto; Yane Devi Anna (Program Studi Keuangan & Perbankan, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2025)
Digital consumer behavior has changed as a result of the growth of global e-commerce, which has also increased attention to sustainable business practices. However, there are many research gaps because companies do not understand the influence of consumer perceptions on financial performance and the lack of stakeholder involvement in supporting green accounting in the e-commerce sector. Using an explanatory quantitative method based on Structural Equation Modeling (SEM) with a Partial Least Squares (PLS) approach, this study aims to address these gaps by examining how the implementation of green accounting positively and significantly impacts financial performance (path coefficient 0.435) and digital consumer perceptions. Profitability is the primary measure of financial performance, while indicators such as resource efficiency and carbon emissions reporting are proven to be dominant in shaping consumer perceptions. These results reinforce the relationship between Signal and Stakeholder theories, emphasizing the importance of sustainability transparency as a tool for communicating with digital consumers. This study contributes to research on digital marketing and sustainable accounting by providing practical guidelines for e-commerce businesses on how to optimize the adoption of green accounting to enhance financial performance and boost consumer trust. Keywords: Green Accounting; Financial Performance; Digital Consumer Perception; Sustainability Transparency; E-Commerce